Cognitive enhancers as a treatment for heroin relapse and addiction. (March 2019) - Ma, Baomiao; Mei, Disen; Wang, Fangmin; Liu, Yu; Zhou, Wenhua
Graphical abstract: Abstract: Heroin addiction is a disorder that stems from maladaptive plasticity within neural circuits and produces broad cognitive deficits. Despite considerable advances in psychotherapy and pharmacotherapy for heroin relapse and addiction, effective treatments for heroin use disorder are still lacking. Increasing preclinical evidence indicates that heroin seeking behavior is persistent after withdrawal, while cognitive dysfunctions associated with chronic heroin use are an important contributing factor to risk of heroin relapse and addiction. Cognitive enhancers may be used to stimulate treatment success and enhance treatment efficacy. The purpose of this review is to outline the literature that demonstrates the cognitive deficits during the development of heroin addiction and withdrawal process, and several factors that underline the efficacy of cognitive enhancers for heroin use disorders. The review, then, examines the potential use and pharmacological mechanisms of cognitive enhancers that act on cholinergic, glutamatergic, dopaminergic or adrenergic pathways. It also examines the effects of compounds that alter CREB signaling and epigenetic mechanisms in animal model of heroin relapse. The current body of research reveals the new insights into the pharmacological mechanisms underlying heroin addiction and holds a significant promise for cognitive enhancers as an improved approach to treat heroin use disorder in a more efficient and persistent way.